P15.05 Performance evaluation of the aptima hiv-1 quant dx assay for detection of hiv-1 in plasma and dried blood spots (dbs). (13th September 2015) - Carrera, A; Sherring, J; McNally, L; Lowe, P; Cunningham, PH
Abstract : Introduction: The Aptima HIV-1 Quant Dx presented on the Hologic PANTHER TM system provides continuous and random access processing of molecular samples for groups M HIV-1 RNA viral load testing. Significant efficiencies are realised through 3.5 h to first result with over 275 samples processed within 8 h. This study assessed the performance of the system in routine plasma samples and whole blood presented as dried blood spot (DBS). Methods: A total of 181 plasma samples were tested over the analytical range and compared to a benchmark real time PCR system. The study focused on the lower analytical range <5, 000 copies/mL HIV-1 RNA (55%). HIV-1 viral load equivalence in non-B subtypes of regional geographical significance was assessed where subtype was available (72%). A further 20 DBS (single 10 mm punch, whole blood) with HIV-1 RNA 500–5, 000 cpy/mL and were eluted using a variety of methods, tested and compared with plasma RNA. Results: Overall, Aptima HIV-1 Quant Dx correlated with the routine analytical platform (r2 = 0.9605). Samples ranged undetectable (16, 8.8%), below the benchmark test lower limit of detection (<20 cpy/ml) (16, 8.8%), low range (20–5, 000) (84, 46.4%), medium (5, 000–50, 000) (36, 19.9%) and high range (>50, 000 cpy/ml) (29, 16%). Samples in the lower analytical range <1, 000 cpy/ml showed little variance when compaired with the Roche (CAP/CTM) assay using Bland-Altman correlation analysis. Reproducibility was assessed in the high, medium and low range within 1–2SD of mean. DBS samples with HIV-1 RNA results >1, 000 were well correlated with plasma. Conclusion: The Aptima HIV-1 Quant Dx automated random access platform correlated with a commonly used HIV RNA test in plasma and offered significant workflow advantages. Promising results obtained using DBS samples could potentially overcome logistics encountered with conventional plasma. Further correlations and limit of detection studies are needed to validated DBS. Disclosure of interest statement: No conflict of interest to declare.